Solvent-engineered morphologies of Mn-MOF toward ultrasensitive sensing cell superoxide. (1st November 2022) - Zhang, Yuhuan; Guo, Chun Xian; Du, Hongfang; Wang, Xingyu; Liu, Liu; Li, Chang Ming
Abstract: It is critical for fabricating ultrasensitive biosensors to realize real-time in situ monitoring of superoxide anions (O2 − ), a typical reactive oxygen species (ROS) that plays critical roles in diverse signaling pathways. Here, a simple on-step strategy was developed for morphology-controllable synthesis of manganese-organic framework (Mn-MOF) toward the enhanced sensing performance of O2 − . Interestingly, by delicately tuning the ratios of solvents to regulate initial concentrations of precursors, Mn-MOF nanoparticles, asymmetric nanolollipops and nanorods all with homogeneous components were prepared. As expected, Mn-MOF nanolollipops outperform other nanostructures in O2 − sensing due to their larger active surface areas which can attribute to their excellent dispersibility provided by the asymmetric structure, and the faster electron transfer rate promoted by the stem. Using the Mn-MOF nanolollipops-based O2 − biosensor, a high sensitivity of 105 μA cm −2 μM −1 is achieved, and the real-time in situ detection of O2 − released from living cells was successfully realized. This work holds a great potential in the exploration of O2 − -related biological processes in vivo, while offering deep scientific insights for solvents engineered morphologies of other MOF nanomaterials. Graphic abstract: Image, graphical abstract